Application of anterior bilateral sacrospinous fixation in the treatment of apical genital prolapse - A. A. Popov; S. A. Gadzhieva (Акушерство, гинекология и репродукция, 2024)
Aim: to increase the clinical effectiveness and safety of apical prolapse treatment by applying anterior bilateral sacrospinous fixation (SSF) with a polypropylene mesh implant.Materials and Methods. A single-center open prospective comparative clinical study in parallel groups in parallel groups was carried out at the Clinic of Academician Krasnopolsky Moscow Regional Research Institute of Obstetrics and Gynecology. There were examined and treated 155 patients with stage II–IV symptomatic genital prolapse according to the Pelvic Organ Prolapse Quantification System (POP-Q) who underwent various variants of SSF. The patients were stratified into 3 groups: group 1 (LPSSF) – 34 patients with symptomatic apical genital prolapse who underwent SSF through the posterior vaginal wall using LPSSF ligatures (ligature posterior sacrospinous fixation); group 2 (LASSF) – 42 patients with symptomatic apical or anterior-apical genital prolapse, who underwent ligature SSF using the anterior approach LASSF (ligature anterior sacrospinous fixation); group 3 (MESH TASSF) – 79 patients with symptomatic apical or anterior-apical genital prolapse, who were treated by applying the anterior bilateral SSF method using synthetic tape MESH TASSF (tape anterior sacrospinous fixation). The frequency of intra- and postoperative complications, patient complaints, and relapse rates were assessed post-surgery. Functional outcomes were assessed using the PFDI-20 questionnaire (Pelvic Floor Distress Inventory-20) at 3, 6 and 12 months after treatment. Patients in group 3 were treated by applying a method we developed for correction of apical genital prolapse and concomitant cystocele reconstruction.Results. The method presented here was characterized by a lower blood volume loss compared to posterior SSF, minimized intra- and postoperative complications: decreased incidence of hematomas, buttock pain, rate of urinary disorders (stress incontinence, mixed forms of urinary incontinence, urgent urinary incontinence, urinary difficulty, bladder hypotension). Applying MESH TASSF fixation allowed to decrease duration of hospital treatment and alleviate pain severity in the postoperative period, and additionally contributed to improved patients' quality of life sustained for as long as 12 months post-surgery.Conclusion. The treatment results confirmed that the MESH bilateral SSF method using an anterior approach is clinically effective, relatively safe, and contributes to a markedly reduced rate of disease relapses. The presence of anterior-apical or apical genital prolapse (C or Ba+C prolapse, stages II–IV according to the POP-Q) should be considered as indications for performing anterior bilateral SSF.